Do the Virtual Communities Match the Real Ones? (Communitarian Perspective) - Jurova, Jarmila (Communications - Scientific letters of the University of Zilina, 2017)
The paper traces the concept of ‘responsive’ (real) community as defined by communitarians. Responsive community is defined as a morally valued way of life characterized by a shared set of values. This concept of community embodies the idea that human beings are fundamentally related to each other through social bonds and value consensus that enable stable relationships among the members. However, a new kind of community – the virtual/online community – has appeared due to the modernization and information technology development in society. Individuals interacting online are often loosely linked by specialized instrumental ties and the boundaries of virtual/online communities seem to be fluid and association among members ephemeral. From the communitarian perspective of a community responsive to the needs of its members as well as demands of society, the author attempts to find out if the virtual communities still meet the conditions of ‘real’ communities.